Desarrollo de la marca “Match Musical”, prototipado de la aplicación web y estrategia de lanzamiento en redes sociales - Monteblanco Pulgar, Katty Nicole (2020)
The music industry in Peru and anywhere in the world is more than just singers or instrumentalists. Over time, getting in touch with someone specific from the world of music was made possible by recommendations from acquaintances. This is how the need arises to create a space that can bring together all these talents: singers and performers, bands, music producers, sound engineers, managers, composers, specialized audiovisual producers, lawyers and dancers, in order to make them "match”, they can show their work, expand their network of contacts and even make a deal. The project consists of appreciating the evolution of Match Musical as a brand, how its graphic identity was determined, how the prototype of the web application was developed using the tools provided by the website template, photomontages adapted to the brand, interactive prototypes made with specialized software and finally the inbound launch strategy that would seek to attract potential customers, through their visits to the web and through specialized content on social networks, with the aim of converting them into leads and registering them, in order to form a community virtual.